Basic ophthalmology - Harper, Richard A. (American Academy of Ophthalmology, 2010)
This concise text is an ideal complement to the medical student curriculum and is an important text for primary care residents and physicians. It features practical information on the diagnosis, management and referral of common ocular disorders and summarizes important ophthalmic concepts, techniques and facts with annotated resources for additional information. This new edition includes updates on neuro-ophthalmology, ocular manifestations of systemic diseases, and drugs and the eye. Additional topics include eye examination, acute and chronic visual loss, the red eye, ocular and orbital injuries, and amblyopia and strabismus.